1995
DOI: 10.3354/meps129113
|View full text |Cite
|
Sign up to set email alerts
|

Time to metamorphosis of blue crab Callinectes sapidus megalopae:effects of benthic macroalgae

Abstract: There is growing evidence that postlarvae (megalopae) of the blue crab Callinectes sapidus can slow the progression through the molt cycle while in offshore nursery grounds, and delay metamorphosis until reinvasion of coastal habitat occurs. However, the cues that trigger metamorphos~s of megalopae are not well known. Thls study tested the hypothesis that the time to metamorphosis (TTM) from the postlarval megalops stage to the first crab stage is shortened in the presence of 2 potential macroalgal settlement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…This result indicates either that water volume was not important, or that the largest test volume was still too different from the natural envlronm.ent to affect time to metamorphosis. Both Forward et al (1994) andBrunlbaugh &McConaugha (1995) found that time to metamorphosis significantly decreased when blue crab megalopae were exposed to estuarine water as compared to times in offshore water The present study found that potency varied between estuaries and cues were associated with many types of estuarine vegetation. Newport River Estuary water contained cues for accelerating metamorphosis.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…This result indicates either that water volume was not important, or that the largest test volume was still too different from the natural envlronm.ent to affect time to metamorphosis. Both Forward et al (1994) andBrunlbaugh &McConaugha (1995) found that time to metamorphosis significantly decreased when blue crab megalopae were exposed to estuarine water as compared to times in offshore water The present study found that potency varied between estuaries and cues were associated with many types of estuarine vegetation. Newport River Estuary water contained cues for accelerating metamorphosis.…”
Section: Discussionmentioning
confidence: 65%
“…Forward et al (1994) found that metamorphosis was accelerated by exposure to estuarine conditions such as low salinity water, estuarine water and the eelgrass Zostera marina. In addition, Brumbaugh & McConaugha (1995) found that the presence of the green alga Ulva lactuca, which is found in estuaries, also reduced the time to metamorphosis. Collectively, these results support the suggestion that metamorphosis is stimulated by estuarine aquatic vegetation (Orth & van Montfrans 1987, Lipcius et al 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Megalopae of the blue crab Callinectes sapidus metamorphose approximately 1 d earlier in estuarine water than in offshore water, and up to 2 d earlier in estuarine water with eelgrass . TTM for blue crab can also be reduced by the addition of the macrophyte Ulva to offshore (but not inshore) water (Brumbaugh & McConaugha 1995), and by lowering the salinity of marsh (but not ocean) water (Wolcott & De Vries 1994). Acceleration of metamorphosis in C. sapidus megalopae is caused by chemical cues from several estuarine plants, but not by structure alone (Forward et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Callinectes sapidus, metamorphosis is delayed by exposure to offshore water , 1996, Wolcott & De Vries 1994, Brumbaugh & McConaugha 1995 but accelerated by exposure to estuarine water (Forward et al , 1996, lower salinity , humic acids (Forward et al 1997), and cues from estuarine aquatic vegetation such as seagrasses (Forward et al , 1996, saltmarsh cord grass (Forward et al 1996) and macroalgae (Brumbaugh & McConaugha 1995, Forward et al 1996. For Uca sp., cues from estuarine sediment (Christy 1989, O'Connor 1991, O'Connor & Judge 1997 (Weber & Epifanio 1996).…”
Section: Introductionmentioning
confidence: 99%